Optimizing Housing Business Decisions with a Spatial Data-Based Point Recommendation System - Jayanti, Wiwik; Yuyun; Nasrullah (Inspiration: Jurnal Teknologi Informasi dan Komunikasi, 2024)
A business point is one of the most important factors as a place to support business activities. In determining the business location point, consideration must first be done carefully and not haphazardly wherever it is, but the location is determined based on careful consideration for reasons of sustainability in the success of the business now and in the future. The aim of this research is to build a system that can recommend determining business points by applying spatial data and implementing the AHP method and TOPSIS method for recommendations for determining housing business points in Mamuju Regency. The methods used in this research are the TOPSIS and AHP methods. Research results from the topsis method trial results with trial results from several alternatives which ranked first were Simboro sub-district with a percentage value of 0.67 and the results of the AHP method trials with several alternatives obtained the top ranking results were Binanga sub-district with a percentage of 0.11. The conclusion of this research is based on the results of a comparison of two methods between the TOPSIS method and the AHP method. The highest level of accuracy is the topsis method.